Plasma amino acids spectrum as an important part of metabolomic pattern in patients with coronary artery disease and atrial fibrillation - I.O. Melnychuk; V.H. Lyzogub (Medičnì Perspektivi)
The aim of our work was to estimate the plasma amino acid (AA) spectrum peculiarities in coronary artery disease (CAD) patients with atrial fibrillation (AF) and to check their connections with cardiometabolic risk factors and gu, microbiota metabolites. 300 patients were divided into three groups: first – 149 patients with CAD but without arrhythmias, second – 123 patients with CAD and AF paroxysm and control group – 28 patients without CAD and arrhythmias. Plasma AA level was detected by ion exchange liquid column chromatography method. The plasma AA spectrum changes in CAD patients with AF paroxysm were investigated: some plasma AA (glutamate, glutamine, glycine, alanine, valine, tyrosine) and their combinations (Isoleucine+Leucine/Valine, Glycine+Serine, Glycine/Methionine, Phenylalanine/Tyrosine, Glutamine/Glutamate) had significant changes in second group patients and had correlations with cardiometabolic risk factors (glycine, valine, arginine, glutamate, isoleucine, alanine, methionine (p<0.05)). Plasma AA combinations were revealed, the lattert could be used as an early marker of AF paroxysm in CAD patients by the results of ROC analysis: 2.44 * Isoleucine – Glycine; area under ROC-curve 0.8122 and 3.16 * Phenylalanine – Glycine, area under ROC-curve 0.8061. Plasma AA spectrum evaluation could be a new promising metabolic marker for AF paroxysm in CAD patients. Altered AA levels point to the depth of pathogenetic changes during AF paroxysm formation: disorders of AA metabolism with branched chain (isoleucine, leucine, valine), aromatic AA (phenylalanine, tyrosine), glutamine/glutamate, glycine/serine and glycine/methionine metabolism. A strong reliable connection between plasma AA spectrum and gut microbiota metabolites (trimethylamine, trimethylamine-N-oxide, total amount of fecal short chain fatty acids) was detected.